Increasing inpatient mortality of nonvariceal upper gastrointestinal bleeding during the COVID-19 pandemic: a nationwide retrospective cohort study. Issue 3 (4th May 2023) - Rasheed, Waqas; Dharmarpandi, Gnanashree; Al-Jobory, Ola; Dweik, Anass; Anil, Muhammad; Islam, Sameer
Abstract: Upper gastrointestinal bleeding results in significant morbidity, mortality, and healthcare burden. This study aimed to evaluate inpatient outcomes of nonvariceal upper gastrointestinal bleeding (NVUGIB) during the year 2020 of the COVID-19 pandemic. The National Inpatient Sample databases were used to identify NVUGIB-related hospitalizations. Outcomes of interest for the year 2019 were compared to 2020 and included inpatient mortality, length of stay, mean inpatient cost, odds of getting esophagogastroduodenoscopy (EGD), mean time to EGD, early EGD (within 1 day of hospitalization), endoscopic intervention for hemostasis, and the odds of developing complications. NVUGIB-related hospitalizations increased by 8.1% in 2020. NVUGIB-related hospitalizations in 2020 were also associated with an 11.1% higher mortality (adjusted odds ratio [aOR] = 1.11, confidence interval [CI] = 1.06–1.17, P  < 0.01), 0.15-day longer mean time to EGD (aOR = 0.15, CI = 0.08–0.24, P  < 0.01), 4% lower odds of getting an EGD (aOR = 0.96, CI = 0.93–0.99, P  = 0.02), 8% lower odds of getting an early EGD (aOR = 0.92, CI = 0.89–0.96, P  < 0.01), and $6340 higher mean inpatient cost (aOR = 6340, CI = 1762–10919, P  = 0.01) compared to 2019. We conclude that there was an increase in NVUGIB-related hospitalizations and mortality in 2020 when the COVID-19 pandemic started.